(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2003)
The methods of revealing the buried morphostructures in the volcanic regions of Armenia by means of the morphological analysis of the relief and the results of the investigations of many years by the authors for this purpose are discussed in the article.